Relationship between pseudo exfoliation syndrome of pupil and increased intraocular pressure and glaucoma in patients referred to ophthalmology clinic of Ardabil city hospital - Ojaghi, Habib; Masoumi, Rahim; Jalalzadeh, Solmaz (International Journal of Research in Medical Sciences, 2017)
Background: Pseudo exfoliation syndrome (PXS) widely in world occurred with various prevalence rate and its risk factor has main role in rising IOP and glaucoma. The aim of this study was to evaluate the relationship between PXS and its associations with elevation of IOP/Glaucoma. Methods: This is a cohort study that has been done on 144 patients of aged 50 and older referred to clinic of ophthalmology which was examined to the PXS depositions. PXS was diagnosed by slit lamp and a control group select matching with case group without PXS. All patients underwent a comprehensive ophthalmic evaluation by slit lamp and dilated pupil fundus for visual acuity, refraction, Tonometry and Gonioscopy. Results: Out of 144 eyes of control group, 112 (77.8%) had PXS depositions. There was a significant increase in number of PXS involved eyes with age and the frequency of disease in men was higher than women. Out of 72 patients, 40 (55.5%) patients were bilaterally and 32 (44.5%) patients were unilaterally involved. The mean of IOP in eyes with PXS with 17.9±8.9 was significantly higher than eyes without PXS with 14.5±2.9. Conclusions: PXS sediments are an important risk factor for increased IOP and glaucoma in our area and patients with PXS should be followed in term of IOP.